Steven Mann’s “Chaos Theory” and Corporate Governance - A. V. Savchenko (Управление)
The article considers the problem of analysis of the external environment of the organization on the basis of the views of Steven Mann’s “theory of controlled chaos”. The use of “chaos theory” allows us to re-evaluate the dynamics of the external environment and to understand the nature of some processes in the world market. “Chaos Theory” is not opposed to the theory of management, but complements it explaining the nonlinearity of the environment and the individual causes of socio-economic viruses.